2002
DOI: 10.1161/01.cir.0000022843.76104.01
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reduces Neointimal Thickening in Low-Density Lipoprotein Receptor–Deficient Mice After Experimental Angioplasty Without Changing Plasma Lipids

Abstract: Background-Statins exert antiinflammatory and antiproliferative actions independent of cholesterol lowering. To determine whether these actions might affect neointimal formation, we investigated the effect of simvastatin on the response to experimental angioplasty in LDL receptor-deficient (LDLR Ϫ/Ϫ ) mice, a model of hypercholesterolemia in which changes in plasma lipids are not observed in response to simvastatin. Methods and Results-Carotid artery dilation (2.5 atm) and complete endothelial denudation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 23 publications
7
61
1
1
Order By: Relevance
“…CRP binds and promotes the clearance of apoptotic cells, sustaining an anti-inflammatory response [36]. While apoptosis is generally associated with suppression of neointimal formation [37,38], CRP-induced clearance of apoptotic cells could explain the reduction in apoptotic cells observed in the CRPtg injured vessel. CRP suppresses neutrophil chemotaxis [39] and superoxide generation [40] that are associated with neointimal formation.…”
Section: Discussionmentioning
confidence: 99%
“…CRP binds and promotes the clearance of apoptotic cells, sustaining an anti-inflammatory response [36]. While apoptosis is generally associated with suppression of neointimal formation [37,38], CRP-induced clearance of apoptotic cells could explain the reduction in apoptotic cells observed in the CRPtg injured vessel. CRP suppresses neutrophil chemotaxis [39] and superoxide generation [40] that are associated with neointimal formation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] These data, as well as accumulating evidence that CRP may have direct inflammatory effects at the endothelial level, and that statin therapy may have important nonlipid anti-inflammatory effects are confirmed by decreasing serum inflammatory markers, such as CRP. 10,12,13 However, limited information has been available in evaluating a potentially effective first 2-week therapeutic approach for the treatment of patients with hypercholesterolemia using 3-hydroxy-3methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor; this issue may be important for patients with acute coronary syndrome. The time course of changes in lipid and lipoprotein levels in the first 2 weeks of therapy with HMG-CoA reductase inhibitor in healthy subjects as well as patients, 6,7 and the rapid reduction in CRP with an 8-week cerivastatin treatment in patients with primary hypercholesterolemia have been demonstrated recently; 11 however, limited data are available in patients with hypercholesterolemia following a 2-week statin therapy.…”
Section: Introductionmentioning
confidence: 93%
“…Numerous trials have indicated the efficacy of statins in CHD, and aggressive lipid lowering, by either diet or combination of diet and drugs, can reduce angina and coronary events after revascularization. [1][2][3][4][5][6][7][8][9][10][11][12][13] When the treatment groups of both primary and secondary prevention trials are compared, the reduction in cardiovascular events is proportional to the reduction in LDL cholesterol levels. 4,5 Therefore, rapid lowering of LDL cholesterol levels may produce early benefit to the coronary endothelium in patients with CHD, and single statin agent therapy may be useful for the management of patients in this high-risk subgroup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, immunohistochemical and Western blot analysis of balloon-injured rat carotid artery showed that a transient increase in phospho-phosphatase and tensin homolog (inactive), a negative regulator of the PI3K/Akt pathway, is correlated to neointimal growth (10). These divergent actions of Akt in endothelial cells and VSMCs synergistically promote neointimal thickening after injury (4). In the present study, exposure of balloon-injured carotid arteries to Ad-Akt WT increased neointimal growth, whereas exposure to Akt kinase-dead AAA mutant (dominant negative) decreased neointimal growth, suggesting the involvement of Akt in neointimal growth.…”
Section: Discussionmentioning
confidence: 99%